THE VIEW OF UTARA PADANG LAWAS SCHOLARS ABOUT THE CULTURE OF ANIMAL SLAUGHTER AT THE TIME OF ACCIDENTS (MAQOSHID SYARIAH) - Hasibuan, Malkan; Siregar, Ramdhan Syahmedi; Nasution, Muhammad Syukri Albani (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This study aims to explore the views of Ulama Padang Lawas Utara regarding the culture of slaughtering animals during misfortunes in the context of Maqoshid Syariah. The research method used is an empirical legal research method with an empirical doctrinal legal approach, through field research. The research respondents consisted of village heads, religious leaders, and community leaders in North Padang Lawas who had an understanding of this issue, as well as the people who practiced this culture. Data collection techniques include interviews and document studies (literature). Data analysis was carried out qualitatively, with the results arranged in the form of sentences arranged systematically. The results of the study show that the views of Ulama Padang Lawas Utara towards the culture of slaughtering animals in times of misfortune state that this tradition is carried out without burdening the grieving family. Costs for animal slaughter are usually collected through the Help-Help Union (STM) and the cooking process is carried out in a collaborative way. In this context, the tradition of slaughtering buffalo is permissible in accordance with the motto "worship side by side", which illustrates the harmonization between traditional traditions and religious teachings.